Analyzing communication skills of Dentistry Post Graduate Residents with Geriatric Patients in Clinical Encounter by using Video Recordings. (June 2023) - Zafar Raja, Hina; Kamran, Rizwana; Farid, Muhammad; Saleem, Muhammad Nasir; Mumtaz, Maryam; Tufail, Shazia; Sarfaraz Khan, Junaid
Background: An effective communication between the doctor and patient is the foremost factor in establishing good interpersonal relationships. This comprises of both verbal and non-verbal communicators. Particularly in the geriatric population, communication can be hindered due to physiological and psychological deterioration. This study was designed to assess the communication skills of dentistry postgraduate residents (PGRs), with their geriatric patients and provide a baseline for the shortcomings and improvements. Methods: Four postgraduate residents of both genders were selected to take clinical interviews of geriatric patients. Audio-video recordings were made by an expert and reviewed by all researchers. The interviews were transcribed individually and thematic analysis was done. Open and axial coding was done for data organization under themes and subthemes. Results: Data transcription led to initial generation of 61 codes. These codes were categorized under nine codes through axial coding and grouping of similar codes. Persistent overlapping of content was found in data transcription, which may indicate data saturation. Conclusion: Workshop-trained postgraduate students of dentistry demonstrated relatively instrumental communication skills at their clinical encounter with geriatric patients. However, the professional demeanor demands further finesse in soft skills, which can be achieved through its regular practice.